AUTOIMMUNE DISEASES: PATHOGENESIS AND THERAPEUTIC STRATEGIES - Dharmesh Singh (TADQIQOTLAR.UZ, 2024)
Abstract: Autoimmune diseases pose significant challenges in both understanding their complex pathogenesis and developing effective treatments. This paper provides an overview of current therapeutic strategies, including conventional therapies such as anti-inflammatory drugs and immunosuppressive agents, as well as emerging approaches like biologics, targeted therapies, and cellular therapies. Challenges in autoimmune disease management, such as treatment resistance, side effects, and the need for personalized treatments, are discussed. The importance of continued research efforts, interdisciplinary collaboration, and innovation in advancing our understanding of autoimmune diseases and improving treatment outcomes is emphasized. Looking ahead, the future landscape of autoimmune disease management holds promise for more personalized, precise, and targeted approaches that optimize treatment outcomes while minimizing side effects. Advances in genomics, immunology, and therapeutic innovation are driving progress towards this goal, with the ultimate aim of enhancing the quality of life for individuals living with autoimmune diseases.